ENHANCING ACCESS TO QUALITY LIFELONG LEARNING OPPORTUNITIES FOR ALL IN NIGERI - Ugwu, Chinwe Uzoma (Journal of Continuing and Development Education, 2025)
This paper explores the critical need for enhancing access to quality lifelong learning opportunities in Nigeria, addressing the multifaceted challenges that hinder participation in educational programmes. The paper identifies key barriers, including inadequate infrastructure, social and cultural stigmas surrounding adult education, and economic constraints that limit access for many individuals. It proposes a comprehensive strategy focused on investing in educational infrastructure, developing digital learning platforms, and fostering community engagement to raise awareness about the importance of lifelong learning. Additionally, the paper emphasizes the need for public-private partnerships and incentives for adult learners to create a more inclusive educational environment. By implementing these strategies, stakeholders can facilitate greater access to lifelong learning, empowering individuals and ultimately contributing to national development and social cohesion in Nigeria